Ukhuwah Islamiyah - Fahril; Dahlan Lama Bawa (Universitas Garut, 2025)
Ukhuwah Islamiyah is a fundamental value in Islamic teachings that plays a crucial role in maintaining unity, harmony, and social stability among Muslims. However, contemporary dynamics such as globalization, identity politics, and the rapid development of digital media pose serious challenges to the strengthening of Muslim brotherhood. This study aims to examine the concept of Ukhuwah Islamiyah, its role in Islamic education, and its relevance in contemporary Muslim social life. This research employs a library research method with a qualitative descriptive approach by analyzing books, scholarly journal articles, and academic documents published from 2015 onwards that are relevant to the research theme. The findings indicate that Ukhuwah Islamiyah is understood as a faith-based bond of brotherhood that generates moral responsibility, social solidarity, and internal tolerance among Muslims. Islamic education plays a strategic role in internalizing the values of ukhuwah through curriculum development, institutional culture, and educators’ role modeling. Furthermore, strengthening Ukhuwah Islamiyah requires support from a moderate religious approach and Islamic value-based digital literacy. This study concludes that Ukhuwah Islamiyah remains highly relevant and needs to be developed systematically and contextually as an effort to strengthen harmony and unity among Muslims in the modern era.